Effects of aging and repeated freeze-thaw cycles on quality attributes, physicochemical and biochemical properties, and sensory characteristics of beef sirloins - Saud Ur Rehman; Jin-Kyu Seo; Madison Romanyk; Dong-Jin Shin; Yuan H. Brad Kim (Applied Food Research)
This study aimed to evaluate the influence of aging before freezing and repeated freezing on quality attributes of beef sirloins. At 5 days postmortem, pairs of sirloins (M. gluteus medius) were collected from 20 beef carcasses (USDA Choice grade). The sirloin samples from each side were assigned to either no additional aging (A0) or 4 weeks of aging (A4). Samples were then subjected to either single freeze-thawing (A0FT and A4FT) or repeated freeze-thawing (A0FT × 2 and A4FT × 2) over 3 weeks. Following aging (2 °C), freezing (−20 °C), and thawing (2 °C), the samples were evaluated for water-holding capacity (WHC), Warner-Bratzler shear force (WBSF), myofibrillar fragmentation index (MFI), color, 2-thiobarbituric acid reactive substances (TBARS), carbonyl and thiol contents, and consumer sensory evaluation (n = 120). Freezing without aging increased freeze-thaw and drip losses in A0FT and A0FT × 2 compared to A4FT and A4FT × 2 (p < 0.05). Freezing and repeated freezing decreased WBSF values (p < 0.05) regardless of aging status. Similarly, MFI was higher in A0FT and A4FT compared to A0 and A4, respectively (p < 0.05). Both freezing and repeated freezing increased TBARS levels (p < 0.05). Moreover, freezing without aging reduced CIE L*, a*, b* and chroma values (p < 0.05). However, aged/frozen samples retained similar color attributes to never frozen counterparts (p > 0.05). Consumer sensory panel reported improved sensory attributes of aged/frozen samples, without any adverse effects from repeated freezing. These findings indicate that aging can improve WHC, color, and tenderness of single or repeated frozen/thawed beef sirloins, suggesting it as a practical strategy for the industry to improve meat quality and value of frozen/thawed beef.